Heating Sizing Power Reduction in Buildings Connected to District Heating with Dynamically Controlled DHW Setback and Flow Limiters - Hatef Hajian; Raimo Simson; Jarek Kurnitski (Energies, 2022)
Space Heating (SH) substations in District Heating-based (DH) systems are typically dimensioned at the design outdoor temperature without accounting for internal and solar heat gains. In residential buildings, the total required DH power typically also includes the need for Domestic Hot Water (DHW). This practice results in oversized substations and high DH design flow rates, which, due to heat gains and building thermal mass utilization in building operation, rarely, if ever, occur. Modern buildings maintain the desired indoor temperature with lower heating power by controlling the SH supply temperature with an outdoor-air-dependent heating curve and heating water flow with room unit thermostats. Applying a dynamic heating control algorithm can be considered one option to reduce the required DH power and optimize the DH network. Another possibility to decrease the needed power is controlling the DH flow by prioritizing DHW production and limiting the DH flow for SH. This study proposed a novel sizing method for the DH substation that quantifies the effects of dynamic control and flow limiters. Building models with detailed hydronic plants, accounting for internal heat gains, and using conventional and dynamic heating controls were developed in the IDA Indoor Climate and Energy simulation tool. The results show a potential DH side power reduction of up to 25%.